2007
DOI: 10.1002/ejic.200700748
|View full text |Cite
|
Sign up to set email alerts
|

Tetranuclear Nickel(II) Complexes Composed of Pairs of Dinuclear LNi2 Fragments Linked by Acetylenedicarboxylate, Terephthalate, and Isophthalate Dianions: Synthesis, Structures and Magnetic Properties

Abstract: The tetranuclear nickel(II) complexes [(LNiII2)2(acetylenedicarboxylate)][BPh4]2 (2[BPh4]2), [(LNiII2)2(terephthalate)][BPh4]2 (3[BPh4]2), and [(LNiII2)2(isophthalate)][BPh4]2(4[BPh4]2), where L2– represents a macrocyclic hexaaza‐dithiophenolate ligand, have been synthesized and characterised by UV/Vis spectroscopy, IR spectroscopy, X‐ray crystallography, and magnetic susceptibility measurements. Each dicarboxylate dianion acts as a quadridentate bridging ligand linking two bioctahedral LNi2 units via μ1,3‐bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…As can be seen, two [Ni 2 L] + units are united by the [Pd(csalen)] complex. The [Ni 2 L(O 2 C R )] + subunits are isostructural with other carboxylate complexes supported by the N 6 S 2 macrocycle 1,2. The carboxylate groups are coordinated in a bidentate bridging mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen, two [Ni 2 L] + units are united by the [Pd(csalen)] complex. The [Ni 2 L(O 2 C R )] + subunits are isostructural with other carboxylate complexes supported by the N 6 S 2 macrocycle 1,2. The carboxylate groups are coordinated in a bidentate bridging mode.…”
Section: Resultsmentioning
confidence: 99%
“…In the past ten years we have reported the synthesis of a number of tetranuclear, mixed ligand complexes of the type [{ M 2 L} 2 {μ‐O 2 C– R –O 2 C}] 2+ , in which { M 2 L} represents a bowl‐shaped complex unit supported by a macrocyclic N 6 S 2 donor ligand that embraces a bridging O 2 C– R –O 2 C 2– dicarboxylate dianion (Figure 1). Typical examples are Ni 4 complexes with acetylenedicarboxylato, terephthalato, isophthalato1 and 1, 1′‐ferrocene dicarboxylato2 ligands. They are readily prepared by substitution reactions between the chlorido‐bridged complex [Ni 2 L(μ‐Cl)] + and the corresponding dicarboxylato dianion 3.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are in the range of those found in mono- and bis(adc) bridged dinuclear and polynuclear compounds. 28 , 29 , 35 , 37 , 38 The selected bond distances and angles are listed in Tables S1 and S2 . A 14-membered ring with dimensions 7.952 Å × 3.277 Å ( Figure 2 ) is formed by two Ni(II) centers, four oxygen atoms, and eight carbon atoms (from both adc).…”
Section: Results and Discussionmentioning
confidence: 99%
“…, in which pairs of bioctahedral [LNi 2 ] 2+ units are joined by a dicarboxylato dianion. 33 In some of these complexes, the carboxylate ions adopt unusual conformations attributable to confinement as for instance in [LNi 2 (μ-3,4dimethyl-6-phenylcyclohex-3-enecarboxylate)], where the phenyl ring and the carboxylate group both assume axial positions with respect to the cyclohexene ring. 34,35 The high carboxylate ion affinity of the [LNi 2 ] 2+ fragment suggested that a selective coordination of amino acids and simple peptides is possible.…”
Section: Introductionmentioning
confidence: 99%